3D printing-assisted osteotomy treatment for the malunion of lateral tibial plateau fracture. Issue 12 (December 2016) - Yang, Peng; Du, Di; Zhou, Zhibin; Lu, Nan; Fu, Qiang; Ma, Jun; Zhao, Liangyu; Chen, Aimin
Abstract: Introduction: Osteotomy and internal fixation are usually the most effective way to treat the malunion of lateral tibial plateau fractures, and the accuracy of the osteotomy is still a challenge for surgeons. This is a report of a series of prospectively study of osteotomy treatment for the malunion of lateral plateau fractures with the aid of 3D printing technology. Methods: A total of 7 patients with malunion of lateral tibial plateau fractures were enrolled in the study between September 2012 to September 2014 and completed follow up. CT image data were used for 3D reconstruction, and individually 3D printed models were used for accurate measurements and detail osteotomy procedures planning. Under the premeditated operation plan, the osteotomy operations were performed. Patients were invited for follow-up examinations at 2 and 6 weeks and then at intervals of 6 to 8 weeks until 12 months or more. Results: Mean age of the patients was 44 years (range 30–52 years), 3 cases were result of fall injuries, 2 were traffic accidents and 2 were sports injuries. Among the cases, one accompanied with craniocerebra trauma, one with pelvic fracture, one accompanied with both. According to the Schatzker Tibial Plateau classification, the original fracture type were 3 type I, 1 type II and 3 type III. The lateral tibial plateau collapse ranges from 4 mm–12 mm, with an average of 9.4 mm. All the operations were successfully completed, the average operation time was 77.1 min (range 70–90 min), the average intraoperative blood loss was 121.4 ml (range 90–180 ml), the mean follow-up time was 14.4 months (range 12–18 months), and the average healing time of the osteotomy fragments was 12 weeks (range 11–13 weeks). The difference between preoperative and postoperative Rasmussen scores were statistically significant (P < 0.05). All the patients were obtained functional recovery, with no complications. Conclusion: 3D printing technology is helpful to accurately design osteotomy operation, reduce the risk of postoperative deformity, decrease intraoperative blood loss, shorten the operation time, and can effectively improve the treatment effect.